Does aid-for-trade from the North promote South-South trade? - Philipp Hühne; Birgit Meyer; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2014)
Our empirical estimations indicate that aid-for-trade granted by OECD donors strengthens the trade relations of recipient countries with other developing countries. By focusing on South-South trade we mitigate endogeneity concerns that have plagued analyses of trade between recipients and donors of aid-for-trade.
Keywords: F14; F35; 330; South-South trade; aid effectiveness; aid-for-trade